Tubulin inhibitors: pharmacophore modeling, virtual screening and molecular docking - NIU Miao-miao; QIN Jing-yi; TIAN Cai-ping; YAN Xia-fei; DONG Feng-gong; CHENG Zheng-qi; FIDA Guissi; YANG Man; CHEN Haiyan; GU Yue-qing (Acta Pharmacologica Sinica, 2016)
Miao-miao NIU#, Jing-yi QIN#, Cai-ping TIAN, Xia-fei YAN, Feng-gong DONG, Zheng-qi CHENG, Guissi FIDA, Man YANG, Hai-yan CHEN, Yue-qing GU* Department of Biomedical Engineering, School of Life Science and Technology, State Key Laboratory of Natural Medicines, China Pharmaceutical University, Nanjing 210009, China Aim: To construct a quantitative pharmacophore model of tubulin inhibitors and to discovery new leads with potent antitumor activities. Methods: Ligand-based pharmacophore modeling was used to identify the chemical features responsible for inhibiting tubulin polymerization. A set of 26 training compounds was used to generate hypothetical pharmacophores using the HypoGen algorithm. The structures were further validated using the test set, Fischer randomization method, leave-one-out method and a decoy set, and the best model was chosen to screen the Specs database. Hit compounds were subjected to molecular docking study using a Molecular Operating Environment (MOE) software and to biological evaluation in vitro. Results: Hypo1 was demonstrated to be the best pharmacophore model that exhibited the highest correlation coefficient (0.9582), largest cost difference (70.905) and lowest RMSD value (0.6977). Hypo1 consisted of one hydrogen-bond acceptor, a hydrogen-bond donor, a hydrophobic feature, a ring aromatic feature and three excluded volumes. Hypo1 was validated with four different methods and had a goodness-of-hit score of 0.81. When Hypo1 was used in virtual screening of the Specs database, 952 drug-like compounds were revealed. After docking into the colchicine-binding site of tubulin, 5 drug-like compounds with the required interaction with the critical amino acid residues and the binding free energies